Integral application of electrical resistivity tomography, geochemistry and borehole data in geoundwater seepage assessment - Hazreek Z.A.M.; Faizal T.B.M.; Aziman M.; Azhar A.T.S.; Fahmy K.A.; Firdaus M.D.M.; Shaylinda M.Z.N.; Hafiz Z.M.; Ashraf M.I.M.; Rozainy M.A.Z.M.; Adnan D.; Aishah M.A.N. (IAEME Publication, 2023)
Electrical resistivity tomography (ERT) has increasingly adopted as an alternative approach in engineering, environmental and archeological studies. In the past, several limitation of conventional method in groundwater mapping was always relative to the high cost, time consuming and limited data coverage. Hence, this study adopted an ERT in order to identify the unknown problematic zone due to the excessive groundwater seepage occurrences. During data acquisition, five (five) ERT spread lines was conducted using ABEM SAS4000 equipment set. Then, field raw data was processed using RES2DINV and ROCKWORKS software to generate 2-D and 3-D of the inverse model resistivity section respectively. Engineering properties and information related to the borehole and geochemistry results was also used for interpretation and verification purposes. Geochemistry test was performed to identify groundwater sources using Atomic Absorption Spectrometer (AAS) and Ion Chromatography (IC) in order to determine the elements of cation (sodium, potassium, calcium and magnesium) and anions (chloride, bicarbonate, nitrate and sulfate) respectively. Based on ERT results, it was found that low electrical resistivity value (10 ~ 100 ?m) which commonly associated to groundwater was detected at ground surface (0 m) until greater depth (> 10 m). Furthermore, it was found that the groundwater was classified as Ca-HCO that indicates the water was originally come from a typical shallow of the fresh groundwater. Finally, this study has successfully demonstrate that the integral application of ERT, geochemistry and borehole data was applicable to produced comprehensive outcome with particular reference to the problematic groundwater seepage assessment. IAEME Publication.